Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Screening and optimisation of crude exopolysaccharide production by marine Brevibacterium sp. JAB08 isolated from the jellyfish Chrysaora sp. from the coastal waters of Goa - Balaji Vaishnavi; R. Amal; Biraja Kumar Sahu; S. V. Sandhya (Antonie van Leeuwenhoek, 2026)

Development of in vitro germination and cryopreservation protocols of pollen in wild Lathyrus species to overcome longevity and asynchronous flowering constraints - Rinky Resma Panda; Padmavati G. Gore; Aishmita Gantait; Esha Singh; Mahesh Rao; S. Rajkumar; Shiv Kumar; Kuldeep Tripathi; Sandhya Gupta (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

In-silico studies on effective phytochemicals of Crocus sativus, Ocimum tenuiflorum and its modifications targeting NIPAH virus - Arsha S. Nair; D. K. S. Lekshmi; Bhavya Bhadran; K. S. Sandhya (In Silico Pharmacology, 2026)

Comparative evaluation of larval susceptibility of Culex quinquefasciatus and Culex gelidus to three formulations of Bacillus thuringiensis var. israelensis - Sandhya Ananth; S. Mahalakshmi; V. Pranav; Dharani Govindasamy; Ashwani Kumar (International Journal of Tropical Insect Science, 2026)

The role of phytochemicals from traditional and medicinal plants in the treatment and inhibition of colon cancer exploring different pathways - Hitarth Sah; Sandhya S (Next Research, 2026)

Hacking heterocysts: advances in the genetic regulation of heterocyst differentiation - Sandhya Deora; G. S. Deora; Subhasha Nigam; Harish (Archives of Microbiology, 2026)

Smart Hybrid Microneedle-Transferosome Platforms for Co-delivery of Peptide Biologics and Gene Modulators: Emerging Horizons in Targeted Transdermal Therapeutics - S. Sandhya; Prakash S. Goudanavar; Prasiddhi Naik (International Journal of Peptide Research and Therapeutics, 2025)

Efficient in vitro regeneration through leaf-derived callus in Origanum majorana (L.): a multipurpose medicinal plant - Dulam Sandhya; Phanikanth Jogam; Gulab Khan Rohela; Syam Prasad Sura; Rajender Vadluri; Mahipal S. Shekhawat; Sadanandam Abbagani (Vegetos, 2025)

Comparative evaluation of pulsed electric field and assisted technology alkalization on the quality characteristics of cocoa powder - S Harish; K Sandhya; Vincent Hema; Ashish Rawson; Venkatachalapathy Natarajan (Innovative Food Science & Emerging Technologies, 2025)

LP-53 Evaluation of the Mutagenic Potential of 1-Cyclopentyl-4-Nitrosopiperazine Nitrosamine in Human Lymphoblastoid TK6and CHO-K1 Cells - M. Shameer P; T. Pradeep; M. Rajini; A. Mariappan; S. Sandhya; G. Kulavardhan; M. Sumithra; R. Harika; A. Varun; K. Mohan; V. Deepa (Toxicology Letters, 2025)

Impact of home gardens promoted among urban residents in Dhaka, Bangladesh - Pepijn Schreinemachers; Sandhya S. Kumar; Nasir Md. Uddin (Food Security, 2025)
Promoting gardening among urban residents holds the potential to improve urban diets in low- and middle-income countries, but there is a lack of evidence of impact. This study tests the hypothesis that training urban residents in gardening increases their intake of fruit and vegetables. It uses panel data for 254 control and 425 treatment households from four city corporations in the Dhaka metropolitan area of Bangladesh. Urban residents, 85% of whom were women, were interviewed before the start of an urban gardening program and one year after training and inputs were provided to the treatment group. The study estimated the average treatment effects using a difference-in-difference estimator. Of the 38 outcomes tested, 20 are significant (p < 0.05) with 19 indicating a beneficial effect and one indicating an adverse effect. Among the beneficial effects, there is an increase in the diversity of fruits and vegetables produced (+ 5 species, p < 0.01), the frequency of harvesting (+ 0.64 times/week; p < 0.01), and increased sharing of produce with neighbors (+ 8%, p < 0.01). Regarding food and nutrition, there is an increase in women’s dietary diversity score (+ 0.37 on a 0–10 scale; p < 0.01), women’s minimum dietary diversity (+ 4%; p < 0.01), and in the number of portions of cooked vegetables eaten (+ 0.96 portions/day; p < 0.01). The gardening intervention also contributes to a range of perceived social, personal, and psychological benefits. The adverse effect is an increase in ultra-processed food consumption (+ 19%, p = 0.04). Nevertheless, the results confirm that urban gardening interventions can improve the quality of urban diets alongside other benefits.

Healing power of Neltuma juliflora (Sw.) Raf.: a comprehensive review of its phytochemicals, pharmacology aspects, and potential health benefits - S. Deepthi; K. Narsimha; K. Ashwini; M. Sandhya Rani; K. Suresh Babu (Natural Product Research, 2025)

Cultivation of Scenedesmus obliquus NCIM 5526 in a sol–gel transition medium for lipid production - V Varshini; R V Anusha Gowri; S Sandhya; L A Nirmal; S Jacob (International Journal of Environmental Science and Technology, 2025)

Processing and utilization of sweet lime pomace in low glycemic wheat flour formulation - Darshan S. Munot; Sandhya R. Shewale; Debashis Kundu (Next Research, 2025)

Electrochemical sensors for monitoring water quality: Recent advances in graphene quantum dot-based materials for the detection of toxic heavy metal ions Cd(II), Pb(II) and Hg(II) with their mechanistic aspects - Saisree S.; Arya S. Nair; Elsa Dais; Sandhya K.Y. (Journal of Environmental Chemical Engineering, 2025)

Dual Metal Ion Sensing by an Azo Compound Derived from Thiazolo[3,2-a] Indole: A Selective and Sensitive Approach - Haitham K.R. Al-Sharifi; C. B. Meenakshy; K. S. Sandhya; Ani Deepthi (Journal of Fluorescence, 2025)

Production of non-embryogenic synthetic seeds for short-term cold storage and ISSR marker-assisted genetic fidelity analysis of Coleus forskohlii (Willd) Briq. plants - Mahesh Kumar Badhepuri; Mahender Aileni; Prabhakar Rao Beeravelli; Sathish Kumar Durgam; Dulam Sandhya; Mahipal S. Shekhawat; Nageswara Rao Singisala (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

A paradigm assessment of low-cost ceramic membranes: Raw materials, fabrication techniques, cost analysis, environment impact, wastewater treatment, fouling, and future prospects - K.V.V. Satyannarayana; Randeep Singh; S. Lakshmi Sandhya Rani; M. Sreekanth; Vinoth Kumar Raja; Young-Ho Ahn (Journal of Water Process Engineering, 2024)

Silver nanoparticle-induced in vitro flowering in Dendrocalamus strictus (Roxb.) nees and genetic fidelity assessment of regenerants using molecular markers - Bharat Singh Rajput; M. Manokari; Nitin J. Solanki; Dulam Sandhya; Mohammad Faisal; Abdulrahman A. Alatar; Mahipal S. Shekhawat (Molecular Biology Reports, 2024)

Proteomic Characterization of Human Placenta: Insights into Potential Therapeutic Applications for Osteoarthritis - Jithu Jerin James; K. V. Sandhya; K. N. Sridhar; S. Sudarson; B. V. Basavaraj; S. Bharath (AAPS PharmSciTech, 2024)

Monitoring genetic transformation with RUBY visible reporter in Nicotiana tabaccum L. - Phanikanth Jogam; Vaishnavi Anumula; Dulam Sandhya; M. Manokari; Ajay Kumar Venkatapuram; V. Mohan Murali Achary; Mahipal S. Shekhawat; Venkataiah Peddaboina; Venkateswar Rao Allini (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Leaf explant based direct and indirect regeneration and SCoT marker assisted genetic fidelity analysis of endemic taxon Corynandra chelidonii var. pallae - Subhash Sirangi; Dulam Sandhya; Gulab Khan Rohela; Mahipal S. Shekhawat; Ragan Ajmeera; Vatsavaya S. Raju (Vegetos, 2023)

Performance of novel pillared eggshell-bentonite clay bio-composite for enhanced phosphate adsorption from aqueous media - Sandhya Sudhakaran; Harsha Mahadevan; Linsha Fathima S; Krishnan Anoop Krishnan (Groundwater for Sustainable Development, 2023)

On drastic change in the relationship between snow cover and Indian monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2023)

Biorecognition elements appended gold nanoparticle biosensors for the detection of food-borne pathogens - A review - Sandhya Sadanandan; Meenakshi V. S; Keerthana Ramkumar; Neeraja P. Pillai; Anuvinda P; Sreelekshmi P. J; Devika V; Ramanunni K; Jeevan Sankar R; M.M. Sreejaya (Food Control, 2023)

Recent advances in Surface Plasmon Resonance (SPR) biosensors for food analysis: a review - Nevetha Ravindran; Sandhya Kumar; Yashini M; Rajeshwari S; Mamathi C A; Nirmal Thirunavookarasu S; Sunil C K (Critical Reviews in Food Science and Nutrition, 2023)

Antimicrobial, antioxidant, cytotoxicity and photocatalytic performance of Co doped ZnO nanoparticles biosynthesized using Annona Muricata leaf extract - P. S. Vindhya; Sandhya Suresh; R. Kunjikannan; V. T. Kavitha (Journal of Environmental Health Science and Engineering, 2023)

Exome sequencing and microarray identified a novel large exonic deletion in SYT2 gene in an ultra-rare case with recessive CMS type 7 - C. P. Ravi Kumar; Parag M. Tamhankar; Radhika Manohar; Sheetal Sharda; G. K. Madhavilatha; S. G. Thenral; Sandhya Nair; A. K. Bojamma (Journal of Genetics, 2022)

Development of efficient Agrobacterium rhizogenes-mediated hairy root system in Curcuma longa L. and elicitation driven enhanced production of pharmaceutically important curcuminoids - S. Sandhya; Archana Giri (In Vitro Cellular & Developmental Biology - Plant, 2022)

Influence of southern hemispheric upper troposphere potential vorticity intrusion events on the southwest monsoon rainfall - M Sandhya; S Sridharan (Journal of Earth System Science, 2022)

Evaluation of the Bioefficacy and Insecticide Compatibility of Entomopathogens for Management of Whitefly (Hemiptera: Aleyrodidae) on Upland Cotton Under Laboratory and Polyhouse Conditions - Satish Kumar Sain; Dilip Monga; Sandhya Kranthi; Neelakanth S. Hiremani; Dipak T. Nagrale; Rishi Kumar; Surender Kumar Verma; Yenumula G. Prasad (Neotropical Entomology, 2022)

Cloning and homologous characterization of geranylgeranyl pyrophosphate synthase (GGPPS) from Withania somnifera revealed alterations in metabolic flux towards gibberellic acid biosynthesis - Yashdeep Srivastava; Sandhya Tripathi; Bhawana Mishra; Neelam S. Sangwan (Planta, 2022)

Advances and prospects in the food applications of pectin hydrogels - Padma Ishwarya S.; Sandhya R.; P. Nisha (Critical Reviews in Food Science and Nutrition, 2022)

Pharmaceutical perspective of neuropathic pain management for primary care providers - Sandhya Jinesh; Justin Kullgren; Gollapudi S. Shankar; Rajan Radhakrishnan (Inflammopharmacology, 2022)

Development of marker-free insect resistant transgenic okra (Abelmoschus esculentus L. Moench) expressing the cry1Ac gene and identification of vector backbone-free events - Satish Deole; Sanjeev Padakipatil; S. R. Sandhya; Asaram Nanote; Murlidhar Jadhav; Pankaj Bihani; Srinivas Parimi; Usha Zehr; M. Narendran; Bharat R. Char (Physiology and Molecular Biology of Plants, 2021)

Sedimentological responses to coastal dynamics along the Thane District, North Maharashtra, West Coast of India - Sridhar D. Iyer; A. R. Gujar; V. Sanil Kumar; D. K. Naik; S. S. Gaonkar; Sandhya Naik; Pooja Shirodkar; F. Badesab; R. A. A. Luis (Sustainable Water Resources Management, 2021)

Comparative transcriptome analyses revealed different heat stress responses in pigeonpea (Cajanus cajan) and its crop wild relatives - G. Ramakrishna; Parampreet Kaur; Anupam Singh; Sunishtha S. Yadav; Sandhya Sharma; N. K. Singh; Kishor Gaikwad (Plant Cell Reports, 2021)

Application of a Two-Analyte Integrated Population Pharmacokinetic Model to Evaluate the Impact of Intrinsic and Extrinsic Factors on the Pharmacokinetics of Polatuzumab Vedotin in Patients with Non-Hodgkin Lymphoma - Dan Lu; Tong Lu; Rong Shi; Leonid Gibiansky; Priya Agarwal; Colby S. Shemesh; Randall C. Dere; Uzor Ogbu; Jamie Hirata; Pascal Chanu; Sandhya Girish; Jin Yan Jin; et al. (Pharmaceutical Research, 2020)
Purpose The established two-analyte integrated population pharmacokinetic model was applied to assess the impact of intrinsic/extrinsic factors on the pharmacokinetics (PK) of polatuzumab vedotin (pola) in patients with non-Hodgkin lymphoma (NHL) following bodyweight-based dosing. Methods Model simulations based on individual empirical Bayes estimates were used to evaluate the impact of intrinsic/extrinsic factors as patient subgroups on Cycle 6 exposures. Intrinsic factors included bodyweight, age, sex, hepatic and renal functions. Extrinsic factors included rituximab/obinutuzumab or bendamustine combination with pola and manufacturing process. The predicted impact on exposures along with the established exposure-response relationships were used to assess clinical relevance. Results No clinically meaningful differences in Cycle 6 pola exposures were found for the following subgroups: bodyweight 100–146 kg versus 38–<100 kg, age ≥ 65 years versus <65 years, female versus male, mild hepatic impairment versus normal, mild-to-moderate renal impairment versus normal. Co-administration of rituximab/obinutuzumab or bendamustine, and change in the pola manufacturing process, also had no meaningful impact on PK. Conclusions In patients with NHL, bodyweight-based dosing is adequate, and no further dose adjustment is recommended for the heavier subgroup (100–146 kg). In addition, no dose adjustments are recommended for other subgroups based on intrinsic/extrinsic factors evaluated.

In vivo evaluation of microbial cocktail of microalgae-associated bacteria in larval rearing from zoea I to mysis I of the Indian white shrimp, Penaeus indicus - S. V. Sandhya; K. P. Sandeep; K. K. Vijayan (Journal of Applied Phycology, 2020)

Population genetic structure of the oceanic whitetip shark, Carcharhinus longimanus, along the Indian coast - S. Sreelekshmi; Sandhya Sukumaran; T. G. Kishor; Wilson Sebastian; A. Gopalakrishnan (Marine Biodiversity, 2020)

Status of Hilsa Fishery in Hooghly-Bhagirathi River System and Associated Coastal Waters of Northern Bay of Bengal - A. M. Sajina; V. R. Suresh; K. M. Sandhya; J. Mukherjee; R. K. Manna; B. K. Behera; R. Samanta; T. Maity; S. K. Banik (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Rational Design, Synthesis, and In Vitro Neuroprotective Evaluation of Novel Glitazones for PGC-1α Activation via PPAR-γ: a New Therapeutic Strategy for Neurodegenerative Disorders - Antony Justin; Subhankar Mandal; P. Prabitha; S. Dhivya; S. Yuvaraj; Pradeep Kabadi; Satheesh John Sekhar; C. H. Sandhya; Ashish D. Wadhwani; Selvaraj Divakar; Jeyabalan Jeyaram Bharathi; Priya Durai; et al. (Neurotoxicity Research, 2020)

Insecticidal activity of botanical oils and other neem-based derivatives against whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) on cotton - Rishi Kumar; Sandhya Kranthi; V. S. Nagrare; D. Monga; Keshav Raj Kranthi; Naveen Rao; Amarpreet Singh (International Journal of Tropical Insect Science, 2019)

Symbiotic association among marine microalgae and bacterial flora: a study with special reference to commercially important Isochrysis galbana culture - S. V. Sandhya; K. K. Vijayan (Journal of Applied Phycology, 2019)

Isolation and phylogenetic identification of heterotrophic thraustochytrids from mangrove habitats along the southwest coast of India and prospecting their PUFA accumulation - K. V. Jaseera; P. Kaladharan; K. K. Vijayan; S. V. Sandhya; M. Leo Antony; M. A. Pradeep (Journal of Applied Phycology, 2019)

Event-Related Potentials in Response to Facial Affect Recognition in Patients with Schizophrenia - G. Sandhya; H. P. Prakash; K. R Nayak; R. V. Behere; P. R. Bhandary; A. S. Chinmay (Neurophysiology, 2019)

Tied up: Does altering phosphoinositide-mediated membrane trafficking influence neurodegenerative disease phenotypes? - Sravanthi S. P. Nadiminti; Madhushree Kamak; Sandhya P. Koushika (Journal of Genetics, 2018)

Re-description of the longtail butterfly ray, Gymnura poecilura (Shaw, 1804) (Gymnuridae: Myliobatiformes) from Bay of Bengal with a neotype designation - M. Muktha; K. V. Akhilesh; S. Sandhya; F. Jasmin; M. A. Jishnudev; Shoba Joe Kizhakudan (Marine Biodiversity, 2018)

Status, Prospects, Threats, and the Way Forward for Sustainable Management and Enhancement of the Tropical Indian Reservoir Fisheries: An Overview - U. K. Sarkar; K. M. Sandhya; P. Mishal; G. Karnatak; S. Kumari; P. Panikkar; R. Palaniswamy; M. Karthikeyan; S. Sibina Mol; T. T. Paul; V. L. Ramya; D. S. K. Rao; et al. (Reviews in Fisheries Science & Aquaculture, 2018)

Light and auxin responsive cytochrome P450s from Withania somnifera Dunal: cloning, expression and molecular modelling of two pairs of homologue genes with differential regulation - Sudhakar Srivastava; Rajender Singh Sangwan; Sandhya Tripathi; Bhawana Mishra; L. K. Narnoliya; L. N. Misra; Neelam S. Sangwan (Protoplasma, 2015)

AECHL-1, a novel triterpenoid, targets tumor neo-vasculature and impairs the endothelial cell cytoskeleton - Aparajita Dasgupta; Mithila A. Sawant; Manish S. Lavhale; Lakshmi-Surekha Krishnapati; Surendra Ghaskadbi; Sandhya L. Sitasawad (Angiogenesis, 2015)

Diurnal variations of the low-level jet over peninsular India during the onset of Asian summer monsoon - Sandhya K. Nair; Thara V. Prabha; N. Purushothaman; S. Sijikumar; S. Muralidharan; N. V. P. Kirankumar; D. B. Subrahamanyam; T. J. Anurose; S. S. Prijith; K. V. S. Namboodiri (Theoretical and Applied Climatology, 2015)

The adenylyl cyclase Rv2212 modifies the proteome and infectivity of Mycobacterium bovis BCG - César Pedroza-Roldán; Michel de Jesús Aceves-Sánchez; Anisha Zaveri; Claudia Charles-Niño; Darwin Eduardo Elizondo-Quiroga; Rodolfo Hernández-Gutiérrez; Kirk Allen; Sandhya S. Visweswariah; Mario Alberto Flores-Valdez (Folia Microbiologica, 2015)

Genotype Frequencies of Drug-Metabolizing Enzymes Responsible for Purine and Pyrimidine Antagonists in a Healthy Asian-Indian Population - Sandhya N. Iyer; Ashwini V. Tilak; Manjari S. Mukherjee; Rekha S. Singhal (Biochemical Genetics, 2012)

Impact of continental meteorology and atmospheric circulation in the modulation of Aerosol Optical Depth over the Arabian Sea - SANDHYA K NAIR; S SIJIKUMAR; S S PRIJITH (Journal of Earth System Science, 2012)

Vertical structure of sea-breeze circulation over Thumba (8.5°N, 76.9°E, India) in the winter months and a case study during W-ICARB field experiment - T. J. Anurose; D. Bala Subrahamanyam; C. B. S. Dutt; N. V. P. Kiran Kumar; Sherine Rachel John; Sandhya K. Nair; M. Santosh; Mannil Mohan; P. K. Kunhikrishnan; S. Sijikumar; S. S. Prijith (Meteorology and Atmospheric Physics, 2012)

Receptor guanylyl cyclase C (GC-C): regulation and signal transduction - Nirmalya Basu; Najla Arshad; Sandhya S. Visweswariah (Molecular and Cellular Biochemistry, 2010)

Agrobacterium-Mediated Transformation of cry1Ac Gene into Shoot-Tip Meristem of Diploid Cotton Gossypium arboreum cv. RG8 and Regeneration of Transgenic Plants - S. B. Nandeshwar; Sandhya Moghe; P. K. Chakrabarty; M. K. Deshattiwar; Keshav Kranthi; P. Anandkumar; C. D. Mayee; B. M. Khadi (Plant Molecular Biology Reporter, 2009)

The Evolution of Guanylyl Cyclases as Multidomain Proteins: Conserved Features of Kinase-Cyclase Domain Fusions - Kabir Hassan Biswas; Avinash R. Shenoy; Anindya Dutta; Sandhya S. Visweswariah (Journal of Molecular Evolution, 2009)

Type-2 diabetes related intermediate phenotypic traits in north Indian diabetics - S. K. Mathur; Piyush Chandra; Sandhya Mishra; Peeyush Ajmera; Praveen Sharma (Indian Journal of Clinical Biochemistry, 2007)

Formulation and evaluation of ketorolac tromethamine-loaded albumin microspheres for potential intramuscular administration - Sam T. Mathew; S. Gayathri Devi; KV Sandhya; KV Sandhya (AAPS PharmSciTech, 2007)

The ascent of nucleotide cyclases: conservation and evolution of a theme - Avinash R. Shenoy; N. Srinivasan; Sandhya S. Visweswariah (Journal of Biosciences, 2002)

Forest change detection in Kalarani round, Vadodara, Gujarat— a Remote Sensing and GIS approach - Jessica P Karia; M C Porwal; P S Roy; G Sandhya (Journal of the Indian Society of Remote Sensing, 2001)

Tyrosine phosphorylation of the human guanylyl cyclase C receptor - Rashna Bhandari; Roy Mathew; K. Vijayachandra; Sandhya S. Visweswariah (Journal of Biosciences, 2000)

Elucidation of the lesions present in the transcription defectivefitA76 mutant ofEscherichia coli: Implication of phenylalanyl tRNA synthetase subunits as transcription factors - Sandhya Ramalingam; M. Hussain Munavar; S. Sudha; A. Ruckmani; R. Jayaraman (Journal of Biosciences, 1999)